Excitation of Alfvén eigenmodes by fusion-born alpha-particles in D-3He plasmas on JET. (1st June 2022) - Kiptily, V G; Kazakov, Ye O; Nocente, M; Ongena, J; Belli, F; Dreval, M; Craciunescu, T; Eriksson, J; Fitzgerald, M; Giacomelli, L; Goloborodko, V; Iliasova, M V; et al.
Abstract: Alfvén eigenmode (AE) instabilities driven by alpha-particles have been observed in D- 3 He fusion experiments on the Joint European Torus (JET) with the ITER-like wall. For the efficient generation of fusion alpha-particles from D- 3 He fusion reaction, the three-ion radio frequency scenario was used to accelerate the neutral beam injection 100 keV deuterons to higher energies in the core of mixed D- 3 He plasmas at high concentrations of 3 He. A large variety of fast-ion driven magnetohydrodynamic modes were observed, including the elliptical Alfvén eigenmodes (EAEs) with mode numbers n = −1 and axisymmetric modes with n = 0 in the frequency range of EAEs. The simultaneous observation of these modes indicates the presence of rather strong alpha-particle population in the plasma with a 'bump-on-tail' shaped velocity distribution. Linear stability analysis and Fokker–Planck calculations support the observations. Experimental evidence of the AEs excitation by fusion-born alpha-particles in the D- 3 He plasma is provided by neutron and gamma-ray diagnostics as well as fast-ion loss measurements. We discuss an experimental proposal for the planned full-scale D-T plasma experiments on JET based on the physics insights gained from these experiments.